PENDAMPINGAN KELOMPOK INFORMASI MASYARAKAT DESA SUMBERDODOL KABUPATEN MAGETAN DALAM PENGEMBANGAN IKLAN PARIWISATA DESA - Tiyas Nur Haryani (Politeknik Negeri Sriwijaya, 2020)
The development of rural tourism is becoming a strategic program in the context of increasing village income. Since the enactment of Law Number 6 of 2014 concerning Villages, villages have more autonomous authority in managing village government management, managing village funds and allocating village funds and managing BUMDes. Village tourism can increase village income and have an impact on improving the welfare of local villagers. Therefore it is interesting to provide assistance for community groups in the village to be able to develop a village tourism program in his village. Science and Technology Activities for the Community we do in Sumberdodol Village, Magetan Regency with Community Information Group partners. Sumberdodol Village is a village that is declared to be one of the tourist villages in Magetan Regency. The main potential of Sumberdodol Village is an abundant spring. The purpose of this IbM activity is to increase the promotion of Sumberdodol Village tourism village through digital media. However, the problem faced by stakeholders is the low level of human resources who dominate the digital promotion media that can increase the promotion of the tourism village of Sumberdodol Village. The methods used in this IbM activity include starting with need assessment, print promotion village training and village tourism e-commerce training.